Carbon Nanotubes – Interactions with Biological Systems - Reis, Joana; Capela-Silva, Fernando; Potes, José; Fonseca, Alexandra; Oliveira, Mónica; Kanagaraj, Subramani; Marques, António Torres (IntechOpen, 2011)
None